Minimal Generators of Annihilators of Even Neat Elements in the Exterior Algebra - ESİN, SONGÜL (Scientific Technical Research Council Turkey-TUBITAK, 2022)
This paper deals with an exterior algebra of a vector space whose base field is of positive characteristic. In this work, a minimal set of generators forming the annihilator of even neat elements of such an exterior algebra is exhibited. The annihilator of some special type of even neat elements is determined to prove the conjecture established in [3]. Moreover, a vector space basis for the annihilators under consideration is calculated.
Keywords: Exterior Algebra; Frobenius Algebra; Symmetric Algebra; Minimal Generators; Annihilator